PEMBUATAN BIOETANOL HASIL HIDROLISA BONGGOL PISANG DENGAN FERMENTASI MENGGUNAKAN SACCAROMYCESS CEREVICEAE - Nurjati Solikhin; Arum Sakti Prasetyo; Luqman Buchori (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Ethanol (C2H5OH) is the liquid from the fermentation of sugars from carbohydrate sources using the help of microorganisms. Bioethanol can also be interpreted as a chemical that is produced from foodstuffs containing starch, such as cassava, sweet potato, corn, and sago.This study was conducted to obtain bioethanol from banana weevil in acid hydrolysis of microbial fermentation and using Saccaromyces cereviceae. In this study using a variable that is fixed for the hydrolysis temperature of 80°C and a concentration of 0.1 N HCl and for fermentation pH:5, temperature: 30°C (room temperature), by microbial Saccaromyces cereviceae. As for the variable change is the addition of starter (4%, 6%, 8% starter) and fermentation time (1 day, 2 day, 3 day, 4 days, 5 days). In this study obtained results that the addition of starter and long variables derived fermentation ethanol content is highest at 4% starter, fermentation 4 days ie 10.03% v / v, for starters 6%, 4 days of fermentation that is 11.19% v/v, and 8% for the starter, fermentation of 5 days ie 12.20% v / v. While the levels of total (ml ethanol / kg of banana weevil) is highest in the addition of starter 8% and 5 days is a long fermentation 912.9003 (ml ethanol / kg of banana weevil). In this fermentation using banana weevil substrate with a water content of 22.25% and glucose levels after hydrolyzed is 13.56%.